MODEL CIRC BERBASIS BING AI DALAM MENULIS PARAGRAF ARGUMENTATIF DAN BERPIKIR KRITIS - Kristiyanto Putra, Awan; Dheni Harmaen (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to investigate the effect of the Cooperative Integrated Reading and Composition (CIRC) model integrated with Bing AI (Copilot) on students' argumentative paragraph writing skills and critical thinking abilities. The research employs a quantitative approach with a quasi-experimental design, specifically a pre-test and post-test control group design. The subjects consist of two classes: the experimental class and the control class, each comprising seven learning groups. The instruments used include writing skill tests, critical thinking tests, student response questionnaires, and observation sheets on learning activities. The results indicate that the post-test scores for both writing and critical thinking in the experimental class were higher than those in the control class. The independent sample t-test revealed statistically significant differences, with Sig. (2-tailed) values of 0.020 for writing and 0.000 for critical thinking. Furthermore, the questionnaire results show that students responded positively to the Copilot-based learning approach, with an average score of 75.00 and consistent score distribution. These findings suggest that the integration of AI technology within collaborative learning enhances 21st-century skills, particularly in constructing arguments and engaging in critical reasoning. It is concluded that the CIRC model supported by Copilot is effective in improving students’ learning outcomes and provides a more structured, reflective, and meaningful learning experience.